Changing modalities in international development and research in education: Conceptual and ethical issues. (October 2019) - Mason, Mark; Crossley, Michael; Bond, Tim
Highlights: A critical examination of changing modalities in international development and related research in education. A critical analysis of North-South research and development partnerships. A critique of the notion of 'best practice' in education and development. A consideration of the issues raised by the emergence of large-scale social and educational research modalities. A discussion of the potential and limitations of 'one size fits all' ethical frameworks in the field. Abstract: This article critically examines the nature of changing modalities in international development and related research in education. The consequences of contemporary trends and trajectories in these domains are considered with particular reference to their conceptual and ethical implications. Drawing on contemporary social theory, comparative and international research in education, and research ethics, the analysis focuses on North-South research and development partnerships, conceptions of 'best practice' in the arenas of education and development, the emergence of large-scale social and educational research modalities, and the potential and limitations of 'one size fits all' ethical frameworks in the field.